"E o verbo se fez bit": uma análise de sites católicos brasileiros como ambiente para a experiência religiosa - Sbardelotto, Moisés (Universidade do Vale do Rio dos Sinos, 2011)
With the manifestation of a phenomenon of appropriation of the Internet by Catholic religious institutions, this research analyzes the operation of the interactions among faithful- Church-God to the living, practice and experience of the faith in the online rituals of the Brazilian Catholic digital environment. It examines in particular, through an analytical methodology, based on the contributions of the systemic and complex thinking, a corpus for research of four Catholic websites: CatolicaNet, Irmãs Apóstolas do Sagrado Coração de Jesus - Província do Paraná, A12 and Fr. Reginaldo Manzotti. It investigates what religion is born from that manifestation of religious practices from the employment and activity of digital media, aiming to collaborate with the analysis of the first direct consequences this phenomenon is bringing to religion, and particularly for the Catholic Church as we know it today. From a reading of some studies that address the interface between communication and religious phenomenon on the Internet, it reflects on some concepts and analytical perspectives for investigating the institutional Catholic Brazilian websites, such as digital mediatization of the religious system; the issue of the technique transformed into media; new modalities of experiencing; and new configurations of time-space-materiality in the religious experience of the faithful. Then, it describes three modalities of supply strategies of the sacred by the system and of appropriation by the faithful in Brazilian Catholic websites, from inferences obtained from our corpus of research: four technological and symbolic levels of interface interactions; four flows of discursive interactions; and two flows, each with two sub-flows, of ritual interactions. In conclusion, it is noted that, through these interactional strategies, the religion that is born in the online environment is lived, practiced, and experienced through new temporalities, new spatialities, new materialities, new discursivities, and new ritualities that are marked by the protocols and processualities of the Internet.
Keywords: Internet; Religião; Midiatização; Interação; Sistema; Religion; Mediatization; Interaction; System; ACCNPQ::Ciências Sociais Aplicadas::Comunicação